From Anti-Judaism to Anti-Semitism ancient and medieval christian constructions of Jewish history - Chazan, Robert Leon 1936-2024 (New York, NY Cambridge University Press, 2016)
The Gospels -- Paul -- Eusebius -- Augustine -- The crusading epoch and spirit: Peter the Venerable -- The discovery of Jewish sources: the Pugio Fidei -- Introduction of medieval slanders: the Fortalitium Fidei -- Looking backward and looking forward: Martin Luther
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Antisemitism -- Europe -- History; Antisemitism -- History; Christianity and antisemitism; Judaism -- Relations -- Christianity -- Middle Ages, 600-1500; Christianity and other religions -- Judaism -- Middle Ages, 600-1500